2007
DOI: 10.1261/rna.694007
|View full text |Cite
|
Sign up to set email alerts
|

Human ribosomal protein L13a is dispensable for canonical ribosome function but indispensable for efficient rRNA methylation

Abstract: Previously, we demonstrated that treatment of monocytic cells with IFN-g causes release of ribosomal protein L13a from the 60S ribosome and subsequent translational silencing of Ceruloplasmin (Cp) mRNA. Here, evidence using cultured cells demonstrates that Cp mRNA silencing is dependent on L13a and that L13a-deficient ribosomes are competent for global translational activity. Human monocytic U937 cells were stably transfected with two different shRNA sequences for L13a and clonally selected for more than 98% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
101
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(110 citation statements)
references
References 89 publications
9
101
0
Order By: Relevance
“…A recent study has also suggested the role of another ribosomal protein, L13a in regulating the cap independent translation of p53, p27 and SNAT2 mRNAs. 34 These observations, together with the current study demonstrating the interaction of PTB with the p53 IRESs, suggest that p53 translation is subject to a multiplicity of controls by differential protein binding that regulates p53 expression. The blots were probed with antibodies against PTB and also antibody corresponding for actin (loading control).…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S supporting
confidence: 59%
“…A recent study has also suggested the role of another ribosomal protein, L13a in regulating the cap independent translation of p53, p27 and SNAT2 mRNAs. 34 These observations, together with the current study demonstrating the interaction of PTB with the p53 IRESs, suggest that p53 translation is subject to a multiplicity of controls by differential protein binding that regulates p53 expression. The blots were probed with antibodies against PTB and also antibody corresponding for actin (loading control).…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S supporting
confidence: 59%
“…Polysome Fraction Analysis-Cytoplasmic extracts were prepared from BM-derived macrophages stimulated with LPS (1 g/ml) as described (31). Cytoplasmic exacts were carefully layered over 5-50% linear sucrose gradients in polysome buffer (10 mM HEPES, pH 7.5, 100 mM KCl, 2.5 mM MgCl 2 , 1 mM dithiothreitol, 50 units of recombinant RNasin (Promega), and 0.1% Igepal-CA630 (Sigma)) and centrifuged at 17,000 rpm in a Beckman SW32.1 Ti rotor for 18 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneously, pre-rRNA are subjected to extensive chemical modifications such as methylations and pseudouridylations (Fromont-Racine et al 2003) at defined sites, and particularly on nucleotides involves in catalysis. The exact function of these modifications is not yet elucidated, but it appears more and more clear that they play a major role in controlling the translational activity of the ribosomes (Yoon et al 2006;Baxter-Roshek et al 2007;Chaudhuri et al 2007). …”
Section: Introductionmentioning
confidence: 99%